2020
DOI: 10.1029/2020wr028049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fracture Roughness on the Onset of Nonlinear Flow

Abstract: In fractures where surface fluctuations are large compared to their aperture (narrow fractures), the flow is forced to move in tortuous paths that produce additional viscous friction and are subject to inertia effects. We consider the relation between the magnitude of surface roughness and the onset of inertial effects in the pressure driving the flow through a single open fracture. We performed experiments systematically varying the average aperture of the open fracture and covering a wide range of Reynolds n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…While the size of low velocity regions increased with the roughness, and the increase of low velocity region led to the stronger heterogeneity of hydraulic characteristics between the area of roughness element and whole flow field in a single fracture. Thus, when RSD > R c , the non-Darcy effect was more likely to occur in fractures with higher roughness, that is, the E d decreased with the increase of roughness which is consistent with other researchers (Cunningham et al, 2020;Qian et al, 2015).…”
Section: Characterizing the Onset Of The Non-darcy Effect Based On Hydraulic Aperturesupporting
confidence: 91%
See 2 more Smart Citations
“…While the size of low velocity regions increased with the roughness, and the increase of low velocity region led to the stronger heterogeneity of hydraulic characteristics between the area of roughness element and whole flow field in a single fracture. Thus, when RSD > R c , the non-Darcy effect was more likely to occur in fractures with higher roughness, that is, the E d decreased with the increase of roughness which is consistent with other researchers (Cunningham et al, 2020;Qian et al, 2015).…”
Section: Characterizing the Onset Of The Non-darcy Effect Based On Hydraulic Aperturesupporting
confidence: 91%
“…Moreover, in previous studies, the critical non‐Darcy effect factor E = 0.1 was used to quantify the onset of non‐Darcy flows, and this criterion has been widely used (Rong et al., 2020; Yu et al., 2017; Zeng & Grigg, 2006; Zhou et al., 2015). However, recent studies showed that geometric properties of single fractures imposed a great influence on the critical value of non‐Darcy effect (Cunningham et al., 2020). Researchers considered that the non‐Darcy effect of fluid flow became non‐negligible when the pressure drop caused by inertial effect accounted for 10% of the total pressure drop ( E = 0.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunningham et al. (2020) showed experimentally on a mated fracture that the Recrit to consider nonlinear effects decreases with increasing local complexity of the fracture void geometry. Thus, both decreasing apertures and an increase in relative aperture fluctuations cause enhanced inertial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Natural fracture surfaces are typically rough with 3D self-affine distribution and display complex hydraulic behavior coming from fracture surface roughness [9]. Fluid flow through individual fractures is affected by multiple factors, such as fracture aperture, surface roughness, and inertial effects, among which aperture and surface roughness may be the two most critical parameters that significantly affect fluid flow behavior [10,11].…”
Section: Introductionmentioning
confidence: 99%